2017
DOI: 10.1111/febs.14118
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of protein tyrosine kinase signalling by Dock and the PTP61F variants

Abstract: Tyrosine phosphorylation-dependent signalling is coordinated by the opposing actions of protein tyrosine kinases (PTKs) and protein tyrosine phosphatases (PTPs). There is a growing list of adaptor proteins that interact with PTPs and facilitate the dephosphorylation of substrates. The extent to which any given adaptor confers selectivity for any given substrate in vivo remains unclear. Here we have taken advantage of Drosophila melanogaster as a model organism to explore the influence of the SH3/SH2 adaptor pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 95 publications
(231 reference statements)
2
10
0
Order By: Relevance
“…Also associated with candidate SNPs are key members of insulin receptor signaling, including foxo , a major transcription factor mediating transcriptomic response to reduced insulin signaling ( Alic et al. 2011 ), dock , which is a negative regulator of insulin signaling ( Willoughby et al. 2017 ), and the fat-body expressed ilp6 , which regulates metabolic response to nutrient shortage ( Chatterjee et al.…”
Section: Resultsmentioning
confidence: 99%
“…Also associated with candidate SNPs are key members of insulin receptor signaling, including foxo , a major transcription factor mediating transcriptomic response to reduced insulin signaling ( Alic et al. 2011 ), dock , which is a negative regulator of insulin signaling ( Willoughby et al. 2017 ), and the fat-body expressed ilp6 , which regulates metabolic response to nutrient shortage ( Chatterjee et al.…”
Section: Resultsmentioning
confidence: 99%
“…Three transcription factors that play a key role in triggering metamorphosis in response to ecdysone ( Eip75B, Kr-h1 and fkh ) are likewise associated with candidate SNPs. Also associated with candidate SNPs are key members of insulin receptor signaling, including foxo , a major transcription factor mediating transcriptomic response to reduced insulin signaling (Alic et al 2011), dock , which is a negative regulator of insulin signaling (Willoughby et al 2017), and the fat-body expressed ilp6 , which regulates metabolic response to nutrient shortage (Chatterjee et al 2014). Interestingly - given the context of chronic nutrient shortage - we found no indication of the nutrient-sensing TOR signaling to have been targeted; none of the 62 genes in the GO term “TOR signaling” was associated with a candidate SNP.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we reasoned that PTPs might play an unappreciated role in cell competition. We selected the Drosophila tyrosine phosphatase protein tyrosine phosphatase 61F ( Ptp61F ) as a candidate, as it has been shown to negatively regulate EGFR-RAS–MAPK and JAK–STAT signalling [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our data thus far have demonstrated a new role for PTP61F as contributing to polarity-impaired cell competition. Previous studies have shown that PTP61F can attenuate JAK–STAT signalling in Drosophila [ 24 , 25 , 26 , 27 , 52 ], but whether PTP61F regulates JAK–STAT signalling in the context of cell competition is unclear. Moreover, although JAK–STAT signalling is known to play a role in the wild-type winner cells during polarity-impaired cell competition [ 53 ], it is unclear whether JAK–STAT signalling has a role within the polarity-impaired loser cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation